Construção de um modelo de dispersão de poluentes na Baía do Guajará - BATISTA, Adriano Gomes (Universidade Federal do Pará, 2014)
The sea and coastal environment of Brazil have suffered a process of considerable environmental degradation in the last years. This degradation was caused by the growing environmental pressure on the sea and the continental natural resources that have overwhelmed the limited capacity of the ecosystems to absorb the impacts. In the specific case of the Bay of Guajará, located in the Estuaries Guajará, in the area delimited by the Bay of Marajó and for the rivers Pará and Guamá, these risks are associated mainly to the pollution originating from of the city of Belém and the petroleum derived pollution caused by transport operations. In the case of the Bay of Guajará, it is known that there are sewer spillings periodically caused by the tide. Because this pollution is caused by the tide, there is little that can be done to correct or soften the effects of this problem. The numeric models consider the complexity of the physical phenomena that govern the operation of the coastal environment, and have been used as tools in hydrodynamic simulation with recognized importance in coastal administration. This application can support several studies: the understanding of the dispersing processes of pollutants; the implantation of systems of monitoring of water quality; the plan of action in cases of a oil spillage; and the effects of alterations in the geometry of channels and bays and estuaries. The objective of this work is to explain these subjects and to describe the necessary stages for the construction of a numeric model of dispersion in the Bay of Guajará using the tools of the Systems of Geographical Information and the Method of Finite Elements.